Ação antioxidante da dieta contendo linalol em juvenis de jundiá (Rhamdia quelen) expostos a hipóxia e reoxigenação - Dornelles, Juan Lameira (2021)
Fish farming is in increasingly developing in Brazilian aquaculture production, stimulating fish prooduction. On the other hand, the increase in stocking density can bring losses to the sector, due to greater exposure of fish to diseases and stress caused by hypoxia, causing reduced immunity and greater susceptibility to diseases. For researchers, there is a need to establish safe and prophylactic nutricional technologies, capable of supporting the growth of the aquaculture chain. Some nutritional alternatives, such as the inclusion of linalool in the feed, have shown great zootechnical success for fish, enhancing their growth and health conditions, without restrictions on the toxicity of the meat towards consumers. The aim of this study was to evaluate the physiological changes of different levels of linalol supplementation in the diet of of juveniles of Rhamdia quelen (jundiás) exposed to hypoxia and reoxygenation, against metabolic and biochemical parameters. For this, the fish were placed in 50 L tanks for 30 days of the experiment, in a water recirculation system and constant aeration. Juveniles were divided int three evaluation groups and submitted to three diets containing different levels of linalol (0-control, 0,25 mL and 1,0 mL of Linalol/kg of feed). Feeding took place throughout the experimental period. Upon reaching 25 days of experiment, a repetition of each treatment was sedated and euthanized. From the 25th to the 26th day, the oxygen dissolved in the water of the remaining animals was reduced, until hypoxia was reached. On the 27th day there was a new euthanasia for tissue collection. Afterwards, the reoxygenation of the thanks was started for 48 hours. On the 30th day of the experiment, the last repetition of juveniles was performed, and the tissues needed for matbolic and biochemical analysis were collected. The results showed a reduction in lactate, total proteins, TBARS, and SOD in animals submitted to diets containing linallol, in a hypoxia and reoxygenation situations, when compared to the control group without the addition of this component to the ration. Thus, we conclude that the use of linalool in the diet of R. quelen juveniles, at the concetrations tested, has an antioxidant function that reduces oxidative stress, with better results at concentrations of 1.0 mL of linalool/kg of feed.